2016
DOI: 10.1007/s10578-016-0629-4
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Autism Spectrum Disorder Traits in Young Children with OCD

Abstract: Studies have shown a high prevalence of autistic spectrum traits in both children and adults with psychiatric disorders; however the prevalence rate has not yet been investigated in young children with OCD. The aim of the current study was to 1.) determine whether ASD traits indicated by the Social Communication Questionnaire (SCQ) and the Social Responsiveness Scale (SRS) were elevated in young children with OCD who do not have a specific ASD diagnosis and 2.) determine if ASD traits were associated with OCD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 34 publications
1
20
1
Order By: Relevance
“…Although prior studies have found that youth with OCD and TD exhibit deficits in social reciprocity (Griffiths et al, 2017; Guler et al, 2015; McGuire et al, 2013; Stewart et al, 2016), our data suggest that these groups exhibit less impairment in social reciprocity domains when compared to neurodevelopmental groups for which social deficits are a hallmark feature (i.e., ASD). Mean group comparisons in our sample suggested that OCD and TD group demonstrated significantly less impairment than ASD and SMD groups in social cognition and social communication, as well as less impairment than the ASD group in social awareness.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Although prior studies have found that youth with OCD and TD exhibit deficits in social reciprocity (Griffiths et al, 2017; Guler et al, 2015; McGuire et al, 2013; Stewart et al, 2016), our data suggest that these groups exhibit less impairment in social reciprocity domains when compared to neurodevelopmental groups for which social deficits are a hallmark feature (i.e., ASD). Mean group comparisons in our sample suggested that OCD and TD group demonstrated significantly less impairment than ASD and SMD groups in social cognition and social communication, as well as less impairment than the ASD group in social awareness.…”
Section: Discussioncontrasting
confidence: 93%
“…Very few studies have examined social reciprocity in youth with other neurodevelopmental disorders. In regard to obsessive-compulsive disorder (OCD) and tic disorder (TD), studies have only examined the affected group (Griffiths et al, 2017; McGuire et al, 2013; Stewart et al, 2016) or compared the affected sample to healthy controls (Guler et al, 2015). Across investigations, findings support the hypothesis that youth with OCD and TD experience elevations in social impairment relative to measurement norms and case controls.…”
Section: Introductionmentioning
confidence: 99%
“…Supplementary measures such as the Social Communication Questionnaire (SCQ) may also be useful in screening for ASD in TS-affected children. 45 In addition, even in the absence of ASD, the SRS may be a very useful tool for identifying children with TS who have such social communication deficits, potentially putting them at increased risk for negative sequelae among their peers.…”
Section: Discussionmentioning
confidence: 99%
“…A few previous studies have addressed the intersection of anxiety and the SRS. Stewart et al [] have shown elevated parent‐report SRS scores for young children in treatment for OCD. In a study of familial transmission of autism traits and anxiety, Duvekot, van der Ende, Constantino, Verhulst, and Greaves‐Lord [] found that mothers' self‐report SRS‐2 scores predicted severity of child anxiety.…”
Section: Introductionmentioning
confidence: 99%